Pengujian Paket Teknologi Budidaya Padi (Oryza sativa L.) - MANALU, FRULIANDONA; DINATA, KETUT KARTHA; ADNYANA, GEDE MENAKA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2012)
ABSTRACT Testing Rice Cultivation Technology Package The purpose of this study was to compare the growth and yield of rice plants cultivated with technology package than the peasant way of rice cultivation. This experiment is a field experiment that compared the cultivation technology package with the way farmers, the observed variables consist of variable growth, yield components, and harvest. Observed variables were compared using the t test 0.05. Experiments conducted in Subak Sempidi, Village Sempidi, District Mengwi, Badung regency, Bali province. The experiment was conducted from May to September 2009. Extensive wetland used 1658 m 2 to 1560 m 2 and a Technology Package for Farmers Cultivation Method. The analysis showed that the treatment was not real different technology packages to farmers cultivating ways. Yields obtained 12.39 tons / ha dry grain harvest for technology packages and 11.47 tons / ha for cultivation dry grain harvest way farmers. Key word : Cultivation Technology Package – Rice
Keywords: Cultivation Technology Package – Rice